Proceedings of the 2nd Workshop on High Performance Computational Finance 2009
DOI: 10.1145/1645413.1645422
|View full text |Cite
|
Sign up to set email alerts
|

Cost vs. performance of VaR on accelerator platforms

Abstract: The computation of value at risk (VaR) can be parallelized to boost performance, but different parallel platforms entail different gains in performance, as well as different costs. This paper explores the cost and performance tradeoffs inherent in the computation of VaR when implemented on different parallel platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A number of financial applications are migrated from small clusters to multi-core and many-core processors which are available at a low budget [31]. For example, research related to financial applications exploiting the Cell BE processor is reported in [32,33].…”
Section: Related Workmentioning
confidence: 99%
“…A number of financial applications are migrated from small clusters to multi-core and many-core processors which are available at a low budget [31]. For example, research related to financial applications exploiting the Cell BE processor is reported in [32,33].…”
Section: Related Workmentioning
confidence: 99%
“…Financial and risk applications in the production setting have progressed from small‐scale clusters to large supercomputers . Recently, an increasing number of financial applications have been migrating from small clusters to multi‐core processors and many‐core accelerators that are available at a low‐cost budget . This includes use of cell broadband engine processors and custom field‐programmable gate arrays architectures .…”
Section: Related Workmentioning
confidence: 99%
“…A number of financial applications are being migrated from small clusters to be hosted on multiple core processors and many core coprocessor which are available at a low budget [12]. For example, research related to financial applications exploiting the Cell BE processor [13] [14], FPGAs [15] [16] and GPUs [17], [18], [19], [20].…”
Section: Related Workmentioning
confidence: 99%